Heterozygous mutations in factor H aggravate pathological damage in a stable IgA deposition model induced by Lactobacillus casei cell wall extract - Li, Jingyi; Dong, Yaping; Chen, Feifei; Yang, Hongyu; Chen, Pei; Li, Hongyu; Shi, Sufang; Zhou, Xujie; Zhu, Li; Zhang, Yuemiao; Liu, Lijun; Xie, Xinfang; et al. (Frontiers in Immunology, 2024)
Activation of complement through the alternative pathway (AP) has a key role in the pathogenesis of IgA nephropathy (IgAN). We previously showed, by intraperitoneal injection of Lactobacillus casei cell wall extract (LCWE), C57BL/6 mice develop mild kidney damage in association with glomerular IgA deposition. To further address complement activity in causing glomerular histological alterations as suggested in the pathogenesis of IgAN, here we used mice with factor H mutation (FH W/R ) to render AP overactivation in conjunction with LCWE injection to stimulate intestinal production of IgA. Dose response to LCWE were examined between two groups of FH W/R mice. Wild type (FH W/W ) mice stimulated with LCWE were used as model control. The FH W/R mice primed with high dose LCWE showed elevated IgA and IgA-IgG complex levels in serum. In addition to 100% positive rate of IgA and C3, they display elevated biomarkers of kidney dysfunction, coincided with severe pathological lesions, resembling those of IgAN. As compared to wild type controls stimulated by the same high dose LCWE, these FH W/R mice exhibited stronger complement activation in the kidney and in circulation. The new mouse model shares many disease features with IgAN. The severity of glomerular lesions and the decline of kidney functions are further aggravated through complement overactivation. The model may be a useful tool for preclinical evaluation of treatment response to complementinhibitors.